THERMAL COMFORT STUDY IN THE AUDITORIUM OF THE FACULTY OF ENGINEERING, PALANGKA RAYA UNIVERSITY - Fredyantoni F. Adji; Onie Dian S; Alderina Rosalia; Elis Sri Rahayu; Theo Fransisco; Audy Mirelia W.S; Taufiqurahman (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2024)
This article examines the thermal conditions and thermal comfort in the Auditorium space at the Faculty of Engineering, Palangka Raya University, focusing on the Auditorium as a case study. This study uses the method of measuring temperature, humidity, and air flow according to the ASHRAE 55 and PMV (Predicted Mean Vote) standards. The results show significant variations in thermal conditions during the use of the study room with a Thermal Sensation index that can affect student concentration. Recommendations for improvement include ventilation arrangements, the use of more efficient building materials, and improving the air conditioning system. These findings are expected to be a reference for improving the quality of the learning environment in educational spaces, especially at the Faculty of Engineering, Palangka Raya University.